Wind velocity extrapolation in Ghana by Weibull probability density function. Issue 1 (February 2018) - Acakpovi, Amevi; Issah, Majeed B; Fifatin, Francois X; Michael, Mathias B
This article proposes a database of reliable wind velocities across the whole Ghana divided into 24 locations, based on data collected for the year 2013, although the bigger plan is to cover the period 2013–2018. For the year 2013 specifically, the proposed data were obtained through extrapolation of RETScreen data on wind velocity in Ghana, originally taken at a height of 10 m to a height of 60 m, adequate for generation using Weibull distribution function. The model led to the determination of the shape factor k and the scale factor c for all the 24 locations which subsequently led to the extrapolated wind velocity. The lowest and highest wind speeds were recorded, respectively, as 3.77 and 8.24 m/s for Wenchi and Wa locations in Ghana. The utmost relevance of this article is of national dimension to Ghana as the resulting wind velocities may be useful to undertake feasibility studies or real implementation of wind power plant.